Is Now the Time for Modern Monetary Theory or Permanent Monetary Finance? - Olaf Schlotmann (Credit and Capital Markets – Kredit und Kapital, 2021)
In response to the COVID-19 pandemic, G7 central banks have launched asset purchase programs in anticipation of an increase in government bond offerings to finance ballooning fiscal deficits. As the volume of government bonds owned by private investors is not expected to rise during the current crisis, these programs will amount to a monetization of large additional debt. The idea that the government sells bonds to the central bank or issues money by literally spending it into existence also plays a key role in Modern Monetary Theory (MMT), the concept of helicopter money and the idea of permanent monetary finance. This article subjects key aspects of MMT to critical examination and shows, using MMT's own balance sheet analysis, that the theory is almost always contradicted by the actual workings of the modern credit economy. In fact, MMT seems to be a collection of prescriptive ideas that dictate how things should function as opposed to how they actually do.
Keywords: E42; E44; E51; E52; E62; H63; B41; E41; 330; Monetary Finance; Modern Monetary Theory; Helicopter Money; Monetary Theory; Balance Sheet Analysis; Theory; Central Banking; Fiscal Policy; COVID-19